Active delivery of multi-layer drug-loaded microneedle patches using magnetically driven capsule. (November 2020) - Lee, Jihun; Lee, Hyoryong; Kwon, Su-hyun; Park, Sukho
Highlights: We proposed an active delivery of multi-layer drug-loaded microneedle (MN) patches using a magnetically driven capsule. Multi-layer MN patches consisting of a MN patch and a PDMS layer were fabricated by a molding method and O2 plasma treatment. The proposed capsule can deliver the multi-layer drug-loaded MN patches easily and accurately to the desired target lesions. Abstract: In this paper, we propose the active delivery of multi-layer drug-loaded microneedle (MN) patches using a capsule that can be driven by an external magnetic field. Firstly, the multi-layer drug-loaded MN patches consist of three delivered MN patches which are composed of a drug-loaded MN patch and polydimethylsiloxane layer. The drug-loaded MN patch is made of a 10% gelatin solution and a drug. The multi-layer MN patches are attached to a permanent magnet in a magnetically driven capsule. Under an external magnetic field generated by an electromagnetic actuation system, the capsule with the multi-layer MN patches can reach the target lesions, and each MN patch can be delivered to the target lesions for medical treatment. The active delivery of the multi-layer MN patches using the proposed magnetically driven capsule was confirmed via phantom experiments. Accordingly, the adhesion of the three separated faces of the multi-layer MN patches and the adhesion between the porcine small intestine and the MN patch were measured using a load cell. We demonstrate the feasibility of the active delivery of the multi-layer MN patches to the target lesions on a porcine small intestine. Consequently, we expect that the active delivery of the multi-layer drug-loaded MN patches using the magnetically driven capsule presented in this study can be a useful method for drug delivery to lesions at various locations in the gastrointestinal tract.